Active sport tourism in Poland: Environmental conditions and motivational aspects - Tomik, Rajmund; Kosmala, Gerard; Ardenska, Agnieszka (European Journal of Geography, 2017)
Active sport tourism has been identified, along with event sport tourism and nostalgia sport tourism, as a category of sport tourism. Active sport tourists travel to participate in sport – being physically active is the main purpose of their travels. Each decision regarding a holiday, weekend or one-day trip is driven by several types of motivation of different intensity and is related to the choice of a destination with desirable environmental conditions. The aim of the study was to analyze the influence of the natural geographical environment variables and motivational forces on the phenomenon of active sport tourism in Poland. The investigations on motivation to participate in active sport tourism were carried out with different fractions of the population of tourists. The analysis of the environmental determinants of active tourism in Poland, such as terrain, climate, air quality and a hydrographic network allow to conclude that the conditions are conducive to different types of active tourism, especially hiking (both lowland and mountain) biking, inland waterway sailing and canoeing. The need to be physically active was the predominant motivation to participate in active sport tourism while ambition was the least important of all motivational dispositions.